Strengths and weaknesses related to the Nurse's role in the Nursing Consultation: Integrative literature review (Research, Society and Development, 2023)
The study aimed to identify the evidence in the literature on the main potentialities and weaknesses related to the Nurse's role in the Nursing Consultation. This is an integrative literature review, carried out from February to March 2023. The data collection resulted in 1,204 articles, of which 475 were in the LILACS database, 247 in SciELO and 482 in BDENF. 1,192 articles were excluded, which did not meet the previously established inclusion and exclusion criteria. Thus, in this integrative review, 12 articles with a predominantly qualitative approach, published between 2009 and 2021, were analyzed. Most of the evaluated studies expose similar difficulties for the operation of the query. Evidences point out that these are related to several factors, such as, for example, lack of scientific knowledge, excessive administrative activities and work overload. They also raise potentiating aspects related to autonomy, professional empowerment and the relevance of the Nurse's work in clinical practice, highlighting the professional-user bond, education and health promotion. The studies presented also reinforce the need for measures that can reduce existing weaknesses, promoting Nursing Consultation and professional autonomy, ensuring comprehensive and quality care. It is relevant that Nurses are able to carry out the consultation, aiming at the constant improvement of assistance and professional recognition. The results indicated reveal the Nursing Consultation as an important assistance tool, however, there are obstacles to its realization.